ANALISIS KARAKTERISTIK PERMUKIMAN UNTUK ESTIMASI TINGKAT KERENTANAN COVID-19 KOTA JAKARTA UTARA BERBASIS INFORMASI GEOGRAFIS - Obed Anderson; Noorlaila Hayati; Yanto Budisusanto (Kokoh, 2022)
This study, an estimation of the vulnerability level of settlements in North Jakarta City was carried out based on the characteristics of settlements (population density, settlement density and accessibility to health centers), and a correlation test was carried out with positive cases of COVID-19 in North Jakarta City in 2020. This study was conducted using Geographic Information System (GIS) technology with spatial buffer, scoring and overlay analysis in estimating the level of vulnerability of the North Jakarta City area to COVID-19 and correlation test with Pearson's Product Moment. Based on the processing, there were 17 villages in the 'safe', 12 wards in the 'vulnerable' class, and 2 'very vulnerable' villages